Body Composition, Eicosapentaenoic Acid, and Vitamin D are Associated with Army Combat Fitness Test Performance - Jeffery L. Heileson; Jared M. McGowen; Jose M. Moris; Tomas J. Chapman-Lopez; Ricardo Torres; LesLee K. Funderburk; Jeffrey S. Forsse (Taylor & Francis Group, 2022)
Background The Army Combat Fitness Test (ACFT), an updated and newly developed metric to assess combat readiness, may require specialized exercise and nutritional interventions. The purpose of this cross-sectional study was to investigate the relationship between body composition, erythrocyte long-chain omega-3 polyunsaturated fatty acids (LC n-3 PUFA), serum vitamin D (VITD) and ACFT performance. Methods Sixty cadets (43 males, 17 females; 20.9 ± 3.8 years; 173.6 ± 10.2 cm; 75.6 ± 13.7 kg) completed the 6-event ACFT (3-repetition maximum trap-bar deadlift [3DL], standing power toss [SPT], hand-release pushups [HRPU], sprint-drag-carry shuttle run [SDC], leg tuck [LTK], or plank [PLK], and 2-mile run [2MR]), body composition analysis via dual-energy x-ray absorptiometry (percent body fat [%BF], lean body mass [LBM], fat-free mass index [FFMI (LBM+bone mineral content)]), and an omega-3 questionnaire. A sub-sample (n = 50) completed blood draws for fatty acid (eicosapentaenoic acid [EPA] and docosahexaenoic acid [DHA]) and VITD analysis. Significance was set at p < .05. Results Lower %BF predicted better performance on all ACFT events (p < .05), except the PLK. Higher LBM was predictive of better performance on the 3DL, SPT, and SDC (p < .05), but no other events. Adjusted FFMI was positively correlated with the 3DL, SPT, HRPU, SDC, and ACFT scores (p < .01 for all). Cadet EPA and DHA dietary intake and omega-3 erythrocyte status was well below established recommendations (25.6 ± 33.9 mg, 58.3 ± 78.1 mg, respectively) and an omega-3 index (O3i = %EPA+%DHA in erythrocytes) of 3.96 ± 1.36%, respectively. EPA was associated with better performance on the 3DL (r = 0.280, p = .049), SPT (r = 0.314, p = .027), LTK (r = 0.316, p = .047), and PLK (r = 0.837, p = .003). After adjusting for body composition, erythrocyte EPA only remained predictive of PLK scores (p = .006). Every 0.1% increase in EPA translated into 5.4 (95% CI: 2.1, 8.8) better PLK score. The O3i or DHA were not associated with any performance variables. Cadets' average serum VITD status was 38.0 ± 14.9 ng∙ml−1. VITD was associated with 3DL (r = 0.305, p = .031), HRPU (r = 0.355, p = .011), 2MR (r = 0.326, p = .021), and total ACFT score (r = 0.359, p = .011). VITD remained predictive of each event after adjustment for body composition. Every 10 ng∙ml−1 increase in VITD was associated with 3-point increase in 3DL, HRPU, 2MR scores, and a 13-point increase in the total ACFT score. Conclusions Our data highlight the importance of measures of muscularity, LBM and FFMI, on ACFT performance. Additionally, EPA and VITD status is associated with various strength, power, and muscular and aerobic endurance components of the ACFT. While these results could help professionals better assess and train military personnel, especially since these measures are modifiable through exercise and dietary interventions, they are ultimately hypothesis generating and warrant further exploration.